Chylomicron retention disease: genetics, biochemistry, and clinical spectrum. Issue 2 (April 2019) - Levy, Emile; Poinsot, Pierre; Spahis, Schohraya
Abstract : Purpose of review: Chylomicron retention disease (CRD) is an autosomic recessive disorder, in which intestinal fat malabsorption is the main cause of diverse severe manifestations. The specific molecular defect was identified in 2003 and consists of mutations in the SAR1B or SARA2 gene encoding for intracellular SAR1B GTPase protein. The aim of this review is first to provide an update of the recent biochemical, genetic and clinical findings, and second to discuss novel mechanisms related to hallmark symptoms. Recent findings: CRD patients present with SAR1B mutations, which disable the formation of coat protein complex II and thus blocks the transport of chylomicron cargo from the endoplasmic reticulum to the Golgi. Consequently, there is a total absence of chylomicron and apolipoprotein B-48 in the blood circulation following a fat meal, accompanied by a deficiency in liposoluble vitamins and essential fatty acids. The recent discovery of Transport and Golgi organization and Transport and Golgi organization-like proteins may explain the intriguing export of large chylomicron, exceeding coat protein complex II size. Hypocholesterolemia could be accounted for by a decrease in HDL cholesterol, likely a reflection of limited production of intestinal HDL in view of reduced ATP-binding cassette family A protein 1 and apolipoprotein A-I protein. In experimental studies, the paralog SAR1A compensates for the lack of the SAR1B GTPase protein. Summary: Molecular testing for CRD is recommended to distinguish the disease from other congenital fat malabsorptions, and to early define molecular aberrations, accelerate treatment, and prevent complications.